Performance under tensile loading of point-by-point wire and arc additively manufactured steel bars for structural components. (July 2021) - Silvestru, Vlad-Alexandru; Ariza, Inés; Vienne, Julie; Michel, Lucas; Aguilar Sanchez, Asel Maria; Angst, Ueli; Rust, Romana; Gramazio, Fabio; Kohler, Matthias; Taras, Andreas
Graphical abstract: Highlights: Build & nozzle angle influence the irregularity of the surface geometry of steel WAAM-bars. Mechanical properties of milled steel WAAM-bars do not depend on build & nozzle angle. Mechanical properties of the steel WAAM-bars are suitable for structural applications. Steel bars produced by wire and arc additive manufacturing exhibit ductile failure. Elastic-plastic models allow predicting the structural behaviour of steel WAAM-bars. Abstract: The point-by-point wire and arc additive manufacturing technology allows precisely depositing of high strength material. In combination with a robotic arm and sensing techniques during printing, it can be used as a novel efficient joining method for custom structural steel components. For accessibility to the parts to be joined, flexibility on the orientation of the printing tool is of high significance. In this contribution, the focus is set on the influence of different printing orientations on relevant properties of point-by-point wire and arc additively manufactured steel bars. Geometry scans show an irregular variation of the cross-section area along the length of the bars. The mechanical properties of the bars are determined from uniaxial tensile tests on as-printed specimens and on locally milled specimens. It is shown, that different printing orientations have an influence on the geometry of the bars, but only a negligible effect on their mechanical properties. The results of the uniaxial tensile tests indicate a good suitability of the additively manufactured steel bars for structural applications. Finite element simulations validate a proposed elastic-plastic material model, which allows predicting the structural behaviour of the point-by-point wire and arc additively manufactured steel bars produced with different printing orientations.